2000
DOI: 10.1097/00004347-200010000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Arrest of Endometrial Epithelium After Paclitaxel Therapy for Breast Cancer

Abstract: We report the histopathologic findings in endometrial curettings from a 31-year-old woman with dysfunctional uterine bleeding who had received paclitaxel therapy for breast carcinoma. Paclitaxel, a member of the taxane family of antineoplastic agents that is used in the treatment of breast carcinoma, ovarian carcinoma, and non-small cell lung carcinoma, acts by the simultaneous promotion of tubulin assembly into microtubules and inhibition of microtubule disassembly. The curettings in this case showed fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Paclitaxel, an MT-stabilizing drugs, induces marked morphologic effect with mitotic arrest in the endometrium (Irving et al 2000). We have recently observed that the treatment with vinblastine or colchicines (MT disrupting drugs) at the concentration between 1 and 100 pM decreased the cAMP-induced IGFBP-1 secretion without changes in cell viability (data not shown).…”
Section: Poly(a)mentioning
confidence: 97%
“…Paclitaxel, an MT-stabilizing drugs, induces marked morphologic effect with mitotic arrest in the endometrium (Irving et al 2000). We have recently observed that the treatment with vinblastine or colchicines (MT disrupting drugs) at the concentration between 1 and 100 pM decreased the cAMP-induced IGFBP-1 secretion without changes in cell viability (data not shown).…”
Section: Poly(a)mentioning
confidence: 97%
“…Subsequent reviews further characterized these changes, and noted a high incidence of ring‐shaped mitotic figures, along with epithelial changes mimicking dysplasia . Similar findings have been described in endometrial epithelium . Such morphologic features are thought to be intrinsically related to the anti‐proliferative effects of taxanes, which function by stabilizing microtubule polymers and arresting cells within metaphase, preventing completion of cell division and triggering apoptosis .…”
Section: Discussionmentioning
confidence: 60%
“…Taxanes act by the simultaneous promotion of tubulin assembly into microtubules and inhibition of microtubule disassembly. In the endometrium, taxane therapy may result in numerous mitoses in metaphase arrest with the formation of ring mitoses 25. Similar morphological changes are seen in other organs, such as the gastrointestinal tract, in association with taxanes.…”
Section: Chemotherapy Induced Changesmentioning
confidence: 74%